Koin NU: A Local Tradition Based Philanthropy Model - Linawati, Linawati; Purwanti, Lilik (Citakonsultindo, 2025)
The purpose of this research is to dissect the mechanism of the Nahdlatul Ulama Charity Box (Koin NU) in the field and the community's response in interpreting the existence of Koin NU and its social impact on society. This is a qualitative study using an interpretative method. The research was conducted in the Ranting NU (NU Branch) of Semen Village, Semen District, Kediri Regency. Data collection used interviews, observation, and document study. The results show that the Koin NU mechanism is a form of local tradition-based philanthropy implemented by the community in terms of mutual cooperation (gotong royong) and a form of compassion (welas asih) towards others. This Koin NU becomes a movement of perpetual charity (amal jariyah) and a spirit of mutual assistance (ta’awun) within the scope of Ahlussunnah wal Jama'ah. The community strongly supports this activity by actively participating in giving charity through Koin NU, which is also interpreted as a form of worship and mutual cooperation to help others, a local tradition that has existed in the community since ancient times.